ENHANCING PARENTS’ PEDAGOGICAL CULTURE: A DISCOURSE ON METHODOLOGICAL SUPPORT (Innovate Conferences, 2025)
This article analyzes the essence and content of the process of enhancing parents’ pedagogical culture, as well as its role and significance in the modern education system.